IMAPACT OF CULTURAL HERITAGE TOURISM-AN OVERVIEW - Shankar, S. (IJRDO -Journal of Computer Science Engineering, 2015)
In general, the world’s leading category of international trade, tourism, is increasingly offering a range of cultural heritage products, from visiting monuments to discovering unique ways of life as supply for increasing cultural and heritage tourism demand. UNESCO defines culture tourism as “to create a discerning type of tourism that takes account of other people’s cultures” . Indeed culture and heritage tourism has been gaining importance recently not only for its’ economic gains but due to more sustainable approaches. As rural and regional economies go through difficult times of change, it may seem to some local communities that heritage can help in terms of economical gains. When what is old and valued in the community can no longer serve its original function, surely it can still attract funding and tourism as a part of cultural heritage. It is a well known fact that a natural link exists between cultural heritage tourism and regional development. Regional development is a key factor which contributes to economic welfare of the host country. The development and application of a system assessing the tourism potential of cultural and heritage assets including cultural, physical, product and experiential values is vital for the sustainability of the tourism attractions. The purpose of this paper is to determine whether there is a link between cultural and heritage tourism and regional development.